The wellness tourist motivation scale: a new statistical tool for measuring wellness tourist motivation. Issue 1 (2nd January 2020) - Kessler, Daniel; Lee, Jun-Hyuk; Whittingham, Nathaniel
ABSTRACT: In the coming years, competition between tourism suppliers for those few individuals who have the health, wealth, and risk profile to travel will be fierce. As it is crucial to understand what motivates wellness tourists, the industry must work with academics to understand the factors which affect motivation. The aim of this exploratory study is twofold. First, this study investigates factors that motivate wellness tourists. Secondly, it seeks to synthesise and validate a wellness tourist motivation scale (WTMS). Study 1 analysed qualitative data from a 2019 industry survey asking respondents about their motivations for going on wellness vacations. Seven motivational dimensions emerged; Movement & Fitness, Healthy Food & Diet, Meditation & Mindfulness, Rest & Relaxation, Learning about Wellness, Self-Care and Nature & Disconnect. From these seven dimensions, wellness tourism industry experts and tourism scholars assisted in creating a survey instrument, representing emergent themes from the data. A Wellness Tourist Motivation Scale (WTMS) was synthesised with twenty-eight items (four motivational items per dimension). In study 2, these twenty-eight statements were tested with 2, 267 survey respondents, of which 93% came from North America. The results give a comprehensive overview of North American-based wellness tourism consumer motivation.